2015
DOI: 10.1001/jamaoto.2015.1560
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Inferior Turbinoplasty for the Treatment of Nasal Obstruction in Children

Abstract: Inferior turbinoplasty showed overall utility and was safe and effective in the treatment of nasal obstruction in children for whom medical management had failed. No differences between surgical techniques were found in patient satisfaction, improvement of nasal patency, and recurrence, likely related to sample size. More than half of the patients continued to use medical therapy postoperatively, suggesting that inferior turbinate hypertrophy should not be considered solely as a surgical disease. Allergic rhin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 13 publications
1
31
0
1
Order By: Relevance
“…Incidentally, we noted that turbinoplasty was performed more frequently in male patients. This finding is consistent with prior studies that showed a male predominance . This may be related to gender differences in the prevalence of rhinitis, but the data in this regard are conflicting.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Incidentally, we noted that turbinoplasty was performed more frequently in male patients. This finding is consistent with prior studies that showed a male predominance . This may be related to gender differences in the prevalence of rhinitis, but the data in this regard are conflicting.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with prior studies that showed a male predominance. 8,14 This may be related to gender differences in the prevalence of rhinitis, but the data in this regard are conflicting. Some studies have demonstrated an increased prevalence of rhinitis in pre-adolescent males, whereas others have shown no significant gender differences.…”
Section: Discussionmentioning
confidence: 99%
“…5 Inferior turbinoplasty (IT) in pediatric patients is a common procedure used to treat childhood nasal obstruction, the goals for the ideal inferior turbinoplasty include maximizing nasal airflow while limiting crusting and synechiae formation by preserving the turbinate mucosa. 6 This is a prospective study included a total of 40 children patients with bilateral nasal obstruction due to bilateral hypertrophied inferior turbinates. Patients did not respond to medical treatment for 3 successive months and all these patients were subjected to turbinate reduction through inferior turbinoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a limited complications profile, laser cautery has never been a commonly used technique in the pediatric population, likely because of the more extensive record of evidence in adults. 15,16 In adults, laser treatment has produced similarly variable efficacy, with studies demonstrating a direct association between the volume of turbinate reduction and degree of mucosal destruction. 22 Thus, more recently developed techniques including submucous debridement and radiofrequency volumetric tissue reduction offer more consistent results with greater preservation of functional mucosal tissue.…”
Section: Resultsmentioning
confidence: 99%